1976
DOI: 10.1203/00006450-197603000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Muscle Mass in Children Using [15N]Creatine

Abstract: Extractcreatine in normal individuals (13,19,21) and is remarkablyIn eight infants and children who had recovered from proteinenergy malnutrition (PEM), muscle mass was estimated by measuring creatine turnover by an isotope dilution technique using [15N]creatine, creatine concentration, and urinary creatinine output. Creatine turnover varied from 1.5 to 2.6% of the muscle creatine pool per day and muscle creatine concentration ranged from 1.7 to 3.9 rglPg muscle D N A . Muscle mass was between 15% and 37% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…These authors have concluded that creatinine output can change independently of lean body mass. The data presented in this and other studies (9,10,25) support the view that there may be considerable error in predicting muscle mass from the daily excretion of urinary creatinine.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…These authors have concluded that creatinine output can change independently of lean body mass. The data presented in this and other studies (9,10,25) support the view that there may be considerable error in predicting muscle mass from the daily excretion of urinary creatinine.…”
Section: Discussionsupporting
confidence: 74%
“…Recently we reported a more direct method of measuring muscle mass in children (25). This method has been used in the present study to determine quantitative changes in muscle mass, total cell number, and functional cell size in malnourished and recovered children.…”
Section: Speculationmentioning
confidence: 99%
See 2 more Smart Citations
“…include diminished creatinine production owing to reduced lean body mass [ 1 ], decreased dietary creatine [2], or reduced body creatine pool [3,4]. Another mechanism for decreased creatinine excretion could be that creatinine produced is accumulated in body fluids.…”
mentioning
confidence: 99%